Low-temperature, simple and efficient preparation of perovskite solar cells using Lewis bases urea and thiourea as additives: stimulating large grain growth and providing a PCE up to 18.8%. Issue 35 (29th May 2018) - Hsieh, Cheng-Ming; Liao, Yung-Sheng; Lin, Yan-Ru; Chen, Chih-Ping; Tsai, Cheng-Min; Wei-Guang Diau, Eric; Chuang, Shih-Ching
Abstract : We demonstrated that urea can be used as an efficient additive for perovskite solar cells with a remarkable performance of 18.8%. Abstract : We demonstrated that two Lewis bases – urea and thiourea – acted as efficient additives for CH3 NH3 (MA)PbI3− x Cl x and MAPbI3 perovskite solar cells (PSCs) and observed a significant increase in PCE for the MAPbI3 devices in the presence of 1% urea with a remarkable PCE of 18.8% using an extremely low annealing temperature (85 °C).